The energy resources of the Arctic region: a view from Russia and Europe - Ruslan Mochalov (European Regional Science Association (ERSA), 2013)
There are some long-term trends in the global energy market: changing geography of hydrocarbons production, displacement of the centers of oil and gas in remote and offshore areas, steady decline in hydrocarbon production in the continental deposits, maintaining a stable level due to increased production from offshore fields. Currently, the share of oil and gas offshore is more than 25% of production in the world. Deterioration of conditions of hydrocarbon production comes with growing demand for oil and gas in the world. According to IEA and BP projections, the global demand for natural gas in 2030 will increase by 40%, oil - by 36%. The Arctic shelf is the largest and still the only source of undiscovered hydrocarbons. According to the U.S. Geological Survey, the share of the Arctic shelf is about one-fifth of all undiscovered recoverable oil and gas reserves in the world. Most of these potential resources are located on the Russian part of the Arctic shelf. Recoverable hydrocarbon resources of the Russian Arctic shelf consist of about 13 billion tons of oil and condensate and 70 trillion cubic meters of natural gas. According to the forecast of the Russian Ministry of Natural Resources, oil production in the Russian Arctic shelf in 2030 will be 66 million tons, and gas production - 230 billion cubic meters. Traditionally, the largest share of Russian exports of oil and gas deal with European countries (about 80%). Supply of Russian energy covers a significant part of the European industry and households needs. In 2012, Russia provided about 34% of natural gas imports the EU, 33% - of crude oil imports. Significant challenges of the development of the Arctic fields are the following: need in more sophisticated and expensive technologies to carry out production and transportation of hydrocarbons in extreme environments, and to provide a sufficient level of environmental safety. To overcome these difficulties, the Russian company Rosneft in 2012 signed an agreement about jointly development the Arctic shelf deposits with foreign companies, ExxonMobil, Statoil, Eni. And in 2013 Russian company Gazprom will start production at the Prirazlomnoye field in the Barents Sea. In the context of sustainable long-term growth in global demand for hydrocarbons offshore development of the Arctic shelf is a necessary condition for energy supply the global economy. Development of new technologies for offshore production and transportation will boost high-tech industries as well as to expand cooperation in the economic and investment areas with the European countries.
Keywords: Q31; 330; Arctic region; energy resourses; hydrocarbons; Russia; Europe